Dual absorber Fe2O3/WO3 host-guest architectures for improved charge generation and transfer in photoelectrochemical applications. (30th January 2017) - Müller, Alexander; Kondofersky, Ilina; Folger, Alena; Fattakhova-Rohlfing, Dina; Bein, Thomas; Scheu, Christina
Abstract: In this study the influence of the spatial distribution and of different nanostructures of WO3 and Fe2 O3 in the dual absorber system Fe2 O3 /WO3 was systematically investigated for the first time. WO3 was applied as a scaffold and/or as a surface treatment to mesoporous Fe2 O3 films. Both approaches strongly increased the performance compared to the individual photoabsorbers. By combining a host guest architecture with a surface treatment, current densities of about 0.7 mA cm −2 at 1.23 V versus reversible hydrogen electrode under AM 1.5 illumination with an incident photon-to-current efficiency of 17% at 350 nm were achieved without the use of further catalysts. We could identify several beneficial interactions between Fe2 O3 and WO3 . WO3 strongly scatters visible light, resulting in increased absorption by Fe2 O3 and higher current densities. We also determined a cathodic shift in the onset potential to 0.8 V and increased transfer rates of up to 88%. This combination of beneficial effects proves the viability of the presented device architecture.